Comprehensive review of greenness, whiteness, and blueness assessments of analytical methods - Sherin F. Hammad; Mohamed A. Adel Hamid; Latifa Adly; Samar H. Elagamy (Green Analytical Chemistry)
In recent years, there has been a growing emphasis on green analytical chemistry GAC to minimize the environmental impact of analytical methods. GAC principles encourage the development of eco-friendly techniques by reducing waste, energy consumption, and harmful reagents. Several tools have been introduced to evaluate the environmental impact of analytical methods, providing numerical or visual representations of their environmental impact. However, many of these tools overlook the crucial role of sample preparation, assuming it can be avoided, which is not always practical. In numerous cases, sample preparation is essential to isolate the desired analyte from complex matrices, ensuring accurate and reliable analysis. Thus, modern assessment tools have evolved to include sample preparation in their evaluation, providing a more comprehensive and fair judgment of the sustainability of the method. Today, various metrics are available to evaluate the sustainability of analytical methods, including green metrics and models for assessing whiteness, blueness, or the practicality of the method. This review will explore and compare these metrics, highlighting their advantages and limitations.